Changes in size-dependent Chlorophyll a concentration and group-specific picophytoplankton abundance in short-term nutrient-addition experiments in the Equatorial Eastern Indian Ocean - Ping Sun; Ping Sun; Kai-Ming Sun; Yuping Zhou; Lu Liu; Chao Yuan; Zongjun Xu; Yan Li; Xuelei Zhang; Zongling Wang (Frontiers in Marine Science, 2024)
To clarify the changes in phytoplankton community and influencing factors in short-term nutrient-addition experiments in the Equatorial Eastern Indian Ocean, we conducted three experiments (one in situ-like experiment, one on-deck experiment with deep seawater, and one on-deck experiment with surface seawater). Our findings indicate that when nutrients were added, there was a more significant increase in the chlorophyll a (chl a) concentrations of microphytoplankton (>20 μm) compared to those of nanophytoplankton (2-20 μm) and picophytoplankton (<2 μm). The chl a concentrations for phytoplankton <20 μm only exhibited significant increases in the on-board incubation of surface seawater collected at 1300 hr when grazing stress have likely been weak. In picophytoplankton, occasional increases in the abundances of Synechococcus were found, while the abundances of Prochlorococcus and eukaryotic picophytoplankton (Peuk) did not increase significantly. It results likely from the preference of grazing effect by herbivores and bottle effects. Additionally, the Prochlorococcus from 75 m was more adapted to weak light, thus its abundance sharply decreased when incubated under high light. We suggest that the nutrient effects have greater influence on microphytoplankton, but other factors, such as grazing and light, might contribute more to <20 μm phytoplankton. Furthermore, bottle effects should be considered when conducting incubation experiments.